Pengaruh Sistem Reward, Work Life Balance, Pengembangan Karier terhadap Retensi Karyawan Melalui Komitmen Organisasi (Studi Kasus di PT Yeon Heung Megasari) - Lilis Setiyani; Slamet Bambang Riono; Andi Yulianto; Hendri Sucipto; Azizah Indriyani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of reward systems, work-life balance, and career development on employee retention, with organizational commitment as a mediating variable at PT Yeon Heung Megasari Brebes. The main issue addressed in this research is the low employee retention rate caused by dissatisfaction with the reward system, imbalance between work and personal life, and limited career development opportunities. This research employs a quantitative approach using a survey method by distributing questionnaires to company employees. The collected data were analyzed using path analysis with Partial Least Squares (PLS). The results indicate that reward systems, work-life balance, and career development have a positive and significant effect on organizational commitment and employee retention. Furthermore, organizational commitment was found to mediate the relationship between the three independent variables and employee retention. These findings suggest that companies should strengthen their reward strategies, work-life balance practices, and career development programs to enhance employee loyalty and workforce sustainability. This research provides theoretical contributions to human resource management and practical recommendations for corporate policy-making.